Pengembangan Populasi Mutan Penanda Aktivasi: I. Transformasi Padi Japonica Tropis Lokal Sulawesi cv. Asemandi dengan bantuan Agrobacterium tumefaciens - Atmitri Sisharmini; Aniversari Apriana; Wening Enggraini; Kurniawan R. Trijatmiko (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2009)
The rice transformation technologyis not only provides valuable methods for the introductionof useful genes into rice plant to improve importantagronomic traits, but also helps in studying gene functionand regulation based on rice genome sequence information.Knockout of genes by insertional mutagenesis is a straightforwardmethod to identify gene functions. One of themethods to develop rice mutants is through genetic transformationmediated by Agrobacterium using activationtagging by Ac-Ds system. A study was done with an objectiveto obtain mutant rice of local tropical japonica cv. Asemandithrough genetic trans-formation mediated by Agrobacteriumtumefaciens. The transformation was conducted usingAgrobacterium vector with the strain of Agl-1 containingactivation tag construct. The result of experiment showedthat it has been obtained 17 independent line (304 plants)transgenic Asemandi containing activation tag construct.These starter lines will be used as materials to developseveral generations of stabil rice mutant through selfing.